Thank You to Our 2019 Peer Reviewers. Issue 17 (2nd September 2020) - Rajaram, Harihar; Camargo, Suzana; Carey, Rebecca; Corey, Rose M.; Dombard, Andrew J.; Donohue, Kathleen A.; Flesch, Lucy; Giannini, Alessandra; Hayes, Gavin; Huber, Christian; Hogg, Andy M.; Ivanov, Valeriy; et al.
Abstract: On behalf of the journal, AGU, and the scientific community, the editors would like to sincerely thank those who reviewed the manuscripts for Geophysical Research Letters in 2019. The hours reading and commenting on manuscripts not only improve the manuscripts but also increase the scientific rigor of future research in the field. We particularly appreciate the timely reviews in light of the demands imposed by the rapid review process at Geophysical Research Letters . With the revival of the "major revisions" decisions, we appreciate the reviewers' efforts on multiple versions of some manuscripts. With the advent of AGU's data policy, many reviewers have helped immensely to evaluate the accessibility and availability of data associated with the papers they have reviewed, and many have provided insightful comments that helped to improve the data presentation and quality. We greatly appreciate the assistance of the reviewers in advancing open science, which is a key objective of AGU's data policy. Many of those listed below went beyond and reviewed three or more manuscripts for our journal, and those are indicated in italics. Key Point: The editors thank the 2019 peer reviewers